2020
DOI: 10.1111/ppl.13239
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and expression profiling of glyoxalase III genes in date palm grown under abiotic stresses

Abstract: Methylglyoxal (MG), a by-product of various metabolic processes, including glycolysis, is a highly reactive cytotoxic metabolite. The level of MG in the cell is maintained at a non-toxic level via MG detoxification pathways such as the universal glyoxalase system, including glyoxalase I/II/III enzymes. Glyoxalase III (DJ-1) can breakdown MG to D-lactate in a single step without reducing glutathione (GSH). Elucidating the function of the DJ-1 gene family may provide further knowledge about its role in plants u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…As a molecular chaperone, DJ‐1 was encoded by parkinson's disease 7 in human beings and has been reported to play an important role in chloroplast development and biotic and abiotic stresses response in plants. [ 41–45 ] We subsequently verified the interaction of TaSnRK1α−1A and TaPAP6L‐2B with TaDJ‐1‐7B in the yeast cell by Y2‐H ( Figure A) and Luciferase Reporter systems, respectively (Figure 3B,C). Subcellular localization in wheat protoplasts showed that Ubi::GFP‐TaDJ‐1 was obviously observed in almost the whole cell (Figure 3D).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…As a molecular chaperone, DJ‐1 was encoded by parkinson's disease 7 in human beings and has been reported to play an important role in chloroplast development and biotic and abiotic stresses response in plants. [ 41–45 ] We subsequently verified the interaction of TaSnRK1α−1A and TaPAP6L‐2B with TaDJ‐1‐7B in the yeast cell by Y2‐H ( Figure A) and Luciferase Reporter systems, respectively (Figure 3B,C). Subcellular localization in wheat protoplasts showed that Ubi::GFP‐TaDJ‐1 was obviously observed in almost the whole cell (Figure 3D).…”
Section: Resultsmentioning
confidence: 76%
“…As a molecular chaperone, DJ-1 was encoded by parkinson's disease 7 in human beings and has been reported to play an important role in chloroplast development and biotic and abiotic stresses response in plants. [41][42][43][44][45] We subsequently verified the interaction of TaSnRK1𝛼−1A and TaPAP6L-2B with TaDJ-1-7B AD-T+BD-53 group was used as positive control, while AD-T+BD-Lam group was used as negative controls. B) Firefly luciferase complementation imaging assay of the interaction between TaSnRK1𝛼−1A and TaPAP6L-2B in tobacco leaves.…”
Section: Tadj-1 As a Molecular Chaperone Possibly Bridged The Interac...mentioning
confidence: 99%
“…Plastids of dj1c plants ( AtDJ1C mutant) showed a lack of thylakoid membranes and granal stacks and homozygous disruption of the AtDJ1C gene resulted in non‐viable, albino seedlings (Lin et al, 2011). Consistently, overexpression of an AtDJ1C ortholog from date palm, PdDJ‐1C in Arabidopsis resulted in an undesired phenotype as it produces non‐viable albino plants (Jana et al, 2021). However, the enzyme kinetics of PdDJ‐1C has not been shown.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, ectopic expression of a DJ‐1_PfpI domain‐containing protein from the wild sugarcane, Erianthus arundinaceus , to a commercial hybrid Co86032, confers tolerance against drought and salinity (Mohanan et al, 2020, 2021). Recently, four DJ‐1 domain‐containing GLY III have been reported in the date palm genome, and overexpression of PdDJ‐1 enhanced growth and reduced MG accumulation in E. coli and yeast hsp31Δ knockout mutant lines in response to carbonyl, oxidative and salinity stress (Jana et al, 2021). However, the enzyme kinetics for PdDJ‐1 has not been shown.…”
Section: Introductionmentioning
confidence: 99%
“… Al-Harrasi et al (2020) isolated a salt-inducible vascular highway 1-interacting kinase ( PdVIK ) and characterized its role in response to various abiotic stresses through heterologous overexpression in yeast and Arabidopsis . Jana and Yaish (2020 , 2021) isolated and characterized the glyoxalase-I gene ( PdGLX1 ) and glyoxalase III genes ( PdDJ-1 ) for their roles in mitigation of abiotic stress tolerance through overexpression in bacterial and yeast systems. This study further suggested that PdGLX1 and PdDJ-1 genes play an important role in methylglyoxal detoxification and in maintaining reactive oxygen species balance under stress conditions in date palms.…”
Section: Date Palm Genomicsmentioning
confidence: 99%